Multifunctional Antibody Agonists Targeting Glucagon‐like Peptide‐1, Glucagon, and Glucose‐Dependent Insulinotropic Polypeptide Receptors. Issue 40 (6th September 2016) - Wang, Ying; Du, Jintang; Zou, Huafei; Liu, Yan; Zhang, Yuhan; Gonzalez, Jose; Chao, Elizabeth; Lu, Lucy; Yang, Pengyu; Parker, Holly; Nguyen‐Tran, Van; Shen, Weijun; et al.
Abstract: Glucagon‐like peptide‐1 (GLP‐1) receptor (GLP‐1R), glucagon (GCG) receptor (GCGR), and glucose‐dependent insulinotropic polypeptide (GIP, also known as gastric inhibitory polypeptide) receptor (GIPR), are three metabolically related peptide hormone receptors. A novel approach to the generation of multifunctional antibody agonists that activate these receptors has been developed. Native or engineered peptide agonists for GLP‐1R, GCGR, and GIPR were fused to the N‐terminus of the heavy chain or light chain of an antibody, either alone or in pairwise combinations. The fusion proteins have similar in vitro biological activities on the cognate receptors as the corresponding peptides, but circa 100‐fold longer plasma half‐lives. The GLP‐1R mono agonist and GLP‐1R/GCGR dual agonist antibodies both exhibit potent effects on glucose control and body weight reduction in mice, with the dual agonist antibody showing enhanced activity in the latter. Abstract : Mono‐ and multifunctional antibody agonists of the receptors GLP‐1R, GCGR, and GIPR were generated by N‐terminal fusion of the exendin‐4, glucagon‐like peptide‐1, glucagon, GIP, and ZP peptides to the heavy chains (HC) and/or light chains (LC) of the humanized monoclonal antibody Synagis. The resulting antibody fusions show excellent activity in sustaining blood glucose control and reducing body weight in rodent models.